"Mahanian" dreams and geopolitical realities: Can India and China co-exist peacefully in the Indian Ocean?. (2nd January 2021) - Bhagawati, Jyotishman
ABSTRACT: The article argues that India and China, in their quest for maritime supremacy in the Indian Ocean, are adopting the seminal ideas and strategies propounded by the celebrated naval strategist and historian, Admiral Alfred Thayer Mahan. It analyses the reasons behind India and China's adoption of the Mahanian naval doctrine and their increasing outreach towards the Indian Ocean region. The article also delves into the implications of following aggressive naval strategies by the two states as well as the discrepancies involved in their respective naval strategies. It concludes by arguing that although the two states are unlikely to engage in a naval war with each other in the foreseeable future, occasional flare-up in hostility and confrontation, as witnessed recently on the land border region of Ladakh, cannot be ruled out as their interests begin to affect each other more in future.